Pan-Hispanic and English Engineering Reference Dictionaries - Jordán, Ramiro (2015)
The Royal Academy of Engineering (RAE) is an active Academy: - Creates value for the Spanish Society through services to their institutions, universities and companies. - Promotes the quality and competence of Spanish Engineering. RAE fosters: - Education, research, innovation, discussion forums. - Dissemination of technology. - Prominent work that advances Engineering.